The effectiveness of the project based learning model in improving students' collaboration skills on creative economic materials - Kinasih, Tita; Ratnawati, Nurul (Universitas Negeri Malang, 2024)
The current learning model emphasizes student involvement, which aims to enable them to participate actively in implementing learning. Collaboration skills are considered one of the critical abilities of the 21st century. These skills are considered to encourage active student participation both in the classroom and in group projects. This research aims to determine the effectiveness of the project-based learning model in improving students' collaboration skills. The research methodology used is quantitative, using a quasi-experimental type. The sample used in this research consisted of 58 students, 29 students in class IX A and 29 in class IX E at MTs Negeri 2 Malang City. The data collection technique uses a research instrument in the form of a questionnaire, while the data analysis technique uses the independent sample t-test. The research results show that applying the project-based learning model significantly influences students' collaborative skills. Implementing a project-based learning model fosters greater student involvement in communication and greater responsibility for the tasks or problems given. The limitations of this research lie in the research respondents. Research respondents were less responsive when filling out the research sample determination questionnaire. This research suggests that the project-based learning model can be an alternative learning model to improve students' collaborative skills. Additionally, further studies might investigate project-based learning models while considering additional characteristics relevant to the 21st century.